2018
DOI: 10.33225/jbse/18.17.590
|View full text |Cite
|
Sign up to set email alerts
|

Science Teachers’ Perceptions of the Emergence of Responsible Research and Innovation in School

Abstract: Responsible Research and Innovation (RRI) has recently gained wider importance in the European Union (EU) as an emergent framework informing the governance of science. While a growing body of literature describing RRI and its main conceptual dimensions has appeared in the last seven years or so and in several policy documents, the European Commission has emphasized the need to promote science education in the RRI context, there is no theoretical elaboration of how RRI can be meaningfully integrated into the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
3
0
2
Order By: Relevance
“…Embora os resultados sejam semelhantes aos encontrados no contexto espanhol (Monge López, 2018), o objetivo deste trabalho não foi encontrar diferenças significativas entre os dois países. Apesar das influências dos contextos culturais, políticos ou econômicos na inovação educativa (Mesquita et al, 2014;Burget et al, 2018;Díaz-Gibson et al, 2019;Fix et al, 2021), aqui é oferecida uma visão atualizada dos principais fatores de inovação em Portugal numa perspectiva que integra o quantitativo e o qualitativo. E isso responde à necessidade de fornecer uma conceituação contextualizada da inovação (Tavares, 2019).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Embora os resultados sejam semelhantes aos encontrados no contexto espanhol (Monge López, 2018), o objetivo deste trabalho não foi encontrar diferenças significativas entre os dois países. Apesar das influências dos contextos culturais, políticos ou econômicos na inovação educativa (Mesquita et al, 2014;Burget et al, 2018;Díaz-Gibson et al, 2019;Fix et al, 2021), aqui é oferecida uma visão atualizada dos principais fatores de inovação em Portugal numa perspectiva que integra o quantitativo e o qualitativo. E isso responde à necessidade de fornecer uma conceituação contextualizada da inovação (Tavares, 2019).…”
Section: Discussionunclassified
“…Por ser um construto socialmente elaborado, há diferenças nas percepções e conceitualizações feitas pelos professores sobre a inovação educativa dependendo da cultura e do país de origem, como Portugal (Mesquita et al, 2014), Estônia (Burget et al, 2018), China (Zhu e Engels, 2014), Espanha (Díaz-Gibson et al, 2019), Países Baixos (Hofman, Jansen e Spijkerboer, 2011;Fix et al, 2021), Estados Unidos (Gray, 2001).…”
Section: Atitudes E Comportamentosunclassified
“…Implementing aspects of democratic citizenship education to foster critical and responsible participation in science education is still challenging for various reasons [48]. Several studies have shown that teachers manifest a relatively limited understanding of what responsible citizenship is and what citizenship education entails; they find challenging the deployment of complex SSIs in their teaching, while there is also a lack of instructional strategies supporting the meaningful integration of RRI into the practice of science education [49][50][51][52][53].…”
Section: Ssibl Pedagogy As An Approach For Responsible Citizenshipmentioning
confidence: 99%
“…This hypothesis is grounded on two different aspects. First, the SSIBL pedagogical framework was designed with a direct aim of enhancing students' responsible citizenship, emphasizing that humans are accountable for the nature and impact of scientific and technological developments, as the essence of RRI [9, [52][53][54]. Second, even though empirical studies reporting on the deployment of SSIBL pedagogy in authentic school classrooms are still limited, a significant corpus of studies has previously deployed SSIBL pedagogy in professional development sessions with science teachers, who have reported on the added value of SSIBL for their teaching [1,7,48,[60][61][62][63][64].…”
Section: Research Questions and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation